Cultural Literacy Based on Ecofeminism: Women's Subsistence in Traditional Folklore of North Sumatera - Elly Prihasti Wuriyani; Wisman Hadi; Mustika Wati Siregar; Siti Maysarah; Tiarma Nova Intan Malasari (Balai Bahasa Provinsi Bali, 2025)
The purpose of this article is to analyze the representation, roles, and forms of women’s subsistence in traditional folklore of North Sumatra through an ecofeminist approach. This study employs a qualitative method using a library research approach. The formal object of the study is literary ecofeminism, which is applied to identify forms of women’s subsistence in sustaining life and adapting to a highly patriarchal social system. The material object consists of 44 folktales from eight indigenous ethnic groups in North Sumatra, namely Batak Toba, Karo, Pakpak, Dairi, Simalungun, Mandailing, Angkola, and Nias. Data were collected through library research by examining primary and secondary sources containing folklore from each ethnic group. The data were analyzed using a dialogical method to integrate various cultural and ecological voices within the texts and to uncover the representation of women’s subsistence in their social and environmental contexts. The results reveal that women in North Sumatran folklore are portrayed as figures shaped by nature, family, and society to sustain their own lives and those around them. Women’s subsistence practices include activities such as agriculture, weaving, livestock raising, fishing, trading, and preparing traditional medicines. These activities symbolize women’s resilience and their contribution to environmental and cultural sustainability. In addition, women are depicted as guardians of moral values and social harmony within their communities. AbstrakTujuan artikel ini adalah untuk menganalisis representasi keberadaan, peran, dan bentuk-bentuk subsistensi perempuan dalam cerita rakyat tradisional di Sumatera Utara melalui pendekatan ekofeminisme. Penelitian ini menggunakan metode kualitatif dengan pendekatan kepustakaan (library research). Objek formal penelitian adalah ekofeminisme sastra yang digunakan untuk mengidentifikasi bentuk-bentuk subsistensi perempuan dalam mempertahankan kehidupan dan beradaptasi dengan sistem sosial yang sangat patrilineal. Objek material berupa 44 cerita rakyat dari delapan etnis asli di Sumatera Utara, yaitu Batak Toba, Karo, Pakpak, Dairi, Simalungun, Mandailing, Angkola, dan Nias. Teknik pengumpulan data dilakukan melalui studi pustaka dengan menelusuri berbagai sumber primer dan sekunder yang memuat cerita rakyat dari masing-masing etnis. Data dianalisis menggunakan metode dialogis untuk menggabungkan berbagai suara budaya dan ekologis dalam teks serta menemukan makna representasi subsistensi perempuan dalam konteks sosial dan lingkungan. Hasil penelitian menunjukkan bahwa perempuan dalam cerita rakyat Sumatera Utara digambarkan sebagai sosok yang dibentuk oleh alam, keluarga, dan masyarakat untuk mempertahankan kehidupan mereka sendiri serta kehidupan orang lain di sekitarnya. Bentuk subsistensi yang dilakukan perempuan mencakup kegiatan pertanian, menenun, memelihara ternak, memancing, berdagang, hingga meramu obat-obatan tradisional. Aktivitas tersebut menjadi simbol ketahanan hidup perempuan dan kontribusinya terhadap keberlanjutan lingkungan dan budaya. Selain itu, perempuan juga digambarkan sebagai penjaga nilai-nilai moral dan keharmonisan sosial dalam masyarakat.